Quality of Public Business Credit Providing Service at BRI Wasuponda Unit, East Luwu District Study of Customer Perception - Nurmilasari Nurmilasari (Journal Of Institution And Sharia Finance, 2021)
This study aims to find out how customers perceive the service quality of people's business loans at PT BANK BRI Wasuponda unit. The research method used is descriptive quantitative. With a population of 250 customers by taking samples using probability sampling techniques and random research samples determined 50 customers. Data analysis used descriptive analysis with frequency distribution analysis tools.The results showed that the customer's perception of the service quality of KUR provision was in the good category with a percentage of 75 ≤ 100% and the affective indicator being the highest aspect with a yield of 1391. This variable was measured through the cognitive aspect with an acquisition percentage of 89.35%, affective with obtaining a percentage of 86.93%, conative with an acquisition of a percentage of 88.75%, tangible with an acquisition of a percentage of 88.16%., reliability with an acquisition of a percentage of 87.87%., Responsiveness with an acquisition of a percentage of 87.5%, assurance with an acquisition of a percentage of 90.12% and empathy with gain of 89.37%.